Automated Guided Vehicle Design Using Inductive Line Following Method On As/rs As A Simulation In Skill Development Center Of Automation Industrial Engineering Faculty Telkom University - Prasetia Pramudita Yuliarso; Haris Rachmat; Tatang Mulyana (eProceedings of Engineering, 2015)
Abstract This paper study about the simulation of how AGV work using RobotinoÂ®. The simulation is needed as a material for studying about AGV. The use of RobotinoÂ® as an AGV because the characteristics is similar with AGV. It will pick up material and transport it from one workstation to another workstation using inductive line as a guidance. After that it arrive in another workstation, it will put down the material on the workstation. To be able to move safely on the inductive line, it can use speed of 200 mm/s. Keywords: AGV, inductive line